2014
DOI: 10.1159/000354320
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art: Sleeve Gastrectomy

Abstract: In the biliopancreatic diversion (BPD) type duodenal switch, sleeve gastrectomy was applied as the restrictive part instead of a horizontal gastrectomy in the original Scopinaro type BPD. Laparoscopic sleeve gastrectomy (LSG) was used as a first step in a staged concept for high-risk patients undergoing bariatric surgery. However, it is now being increasingly favored as a stand-alone procedure. This article discusses the history, surgical technique, early results, metabolic effects, mid- to long-term results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…In revisional bariatric surgery, the risk for surgical complications is higher and complications might be more difficult to treat [1,11]. In the present series, we recorded one (5.9%) early complication with a leak at the angle of His within the first week after re-SG.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In revisional bariatric surgery, the risk for surgical complications is higher and complications might be more difficult to treat [1,11]. In the present series, we recorded one (5.9%) early complication with a leak at the angle of His within the first week after re-SG.…”
Section: Discussionmentioning
confidence: 51%
“…In SG, Baltasar et al reported first on two patients who had undergone re-SG for dilation of SG, with subsequent increased successive weight loss [23]. Other authors reported comparable observation with a substantial of weight regain in up to 23% of SG [5,6,11,18]. However, consideration should be given to a possible re-SG since additional gastric volume restriction might jeopardize the patient's psychological balance [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations